2018
DOI: 10.1186/s12879-017-2928-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing microbial colonies in the air of operating rooms

Abstract: BackgroundThe operating room (OR) of the hospital is a special unit that requires a relatively clean environment. The microbial concentration of an indoor OR extrinsically influences surgical site infection rates. The aim of this study was to use active sampling methods to assess microbial colony counts in working ORs and to determine the factors affecting air contamination in a tertiary referral medical center. MethodsThis study was conducted in 28 operating rooms located in a 3000-bed medical center in north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 25 publications
4
60
2
4
Order By: Relevance
“…Theatre management techniques such as reducing the amount of staff present to the minimum and utilizing laminar flow systems are well established, 25 and were already in use prior to 2013. However, the MDT analysis determined that there was no established protocol for surgical glove changes.…”
Section: Discussionmentioning
confidence: 99%
“…Theatre management techniques such as reducing the amount of staff present to the minimum and utilizing laminar flow systems are well established, 25 and were already in use prior to 2013. However, the MDT analysis determined that there was no established protocol for surgical glove changes.…”
Section: Discussionmentioning
confidence: 99%
“…Under air circulation, the microbial colonies can be significantly reduced by 77.3%-79.3% within the first 30 minutes, and up to 96.4%-99.5% within 75 minutes. 46 Digital patient follow-up. It is recommended to follow up with patients digitally through photographs or video calls using the phone or other communication tools, such as WeChat and WhatsApp, to not only monitor the orthodontic progress but also to minimize the repeated patient contact and ensure patient safety in case of orthodontic emergencies.…”
Section: Management For Reusable Items and Medical Wastesmentioning
confidence: 99%
“…In operating theatres, airborne virus particles can be diluted by supplied air, with air then flowing to less sensitive areas. In addition, studies have shown that the airborne microbe counts increase with the degree of movement and personnel numbers, 15 supporting the decision to have only one radiologist and anaesthetist physically present in the scanning room. The principle of modern theatre ventilation is to remove airborne contamination generated in the room and to prevent the ingress of contaminated air from surrounding areas.…”
Section: Discussionmentioning
confidence: 97%